2015
DOI: 10.1161/jaha.115.002072
|View full text |Cite
|
Sign up to set email alerts
|

N‐Terminal Pro–Brain Natriuretic Peptide (NT‐proBNP) Levels are Increased in Patients With Transient Ischemic Attack Accompanied by Nonfocal Symptoms

Abstract: BackgroundTransient nonfocal neurological symptoms may serve as markers of cardiac dysfunction. We assessed whether serum N‐terminal pro–brain natriuretic peptide (NT‐proBNP) levels, a biomarker of cardiac disease, are increased in patients with transient ischemic attack (TIA) accompanied by nonfocal symptoms and in patients with attacks of nonfocal symptoms (transient neurological attack [TNA]).Methods and ResultsWe included 15 patients with TNA, 69 with TIA accompanied by nonfocal symptoms, 58 with large‐ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Nevertheless, in our study sample, patients with TNAs were not more likely to have vascular risk factors, such as hypertension, lipid-lowering medication or diabetes mellitus than participants without TNAs. Second, cognitive impairment could be the result of cerebral hypoperfusion, which has long been suggested a potential cause of TNAs [1, 2, 29]. This concurs with the results of a large, population-based study in which cerebral hypoperfusion is associated with accelerated cognitive decline [30].…”
Section: Discussionsupporting
confidence: 76%
“…Nevertheless, in our study sample, patients with TNAs were not more likely to have vascular risk factors, such as hypertension, lipid-lowering medication or diabetes mellitus than participants without TNAs. Second, cognitive impairment could be the result of cerebral hypoperfusion, which has long been suggested a potential cause of TNAs [1, 2, 29]. This concurs with the results of a large, population-based study in which cerebral hypoperfusion is associated with accelerated cognitive decline [30].…”
Section: Discussionsupporting
confidence: 76%
“…Two previous studies have found indirect evidence for a cardiac origin, as patients with nonfocal symptoms had a high risk of major cardiac events during follow-up [1,6] . A recent study showed increased NT-proBNP levels in patients with TIA accompanied by nonfocal symptoms [9] . Another study found brady arrhythmias in a subgroup of patients aged under 30 [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Positive nonfocal symptoms might by caused by an epileptic or migraine-like phenomena, whereas negative nonfocal symptoms are due to cardiac rhythm and conduction disorders, heart failure, or ischemic heart disease, which may directly lead to nonfocal symptoms by causing a sudden reduction in cerebral blood flow or indirectly by anxiety-induced hyperventilation. In a recent study, we found that NT-proBNP levels are increased in patients with TIA accompanied by nonfocal symptoms, suggesting that temporary nonfocal symptoms serve as markers of cardiac dysfunction [9] . Furthermore, a recent study showed that patients with attacks with nonfocal symptoms were associated with frontoparietal cortical ischemia on either side [10] .…”
Section: Introductionmentioning
confidence: 89%
“…Consensus on the etiology of TNAs and its pathogenesis is still lacking. Both transient and chronic global cerebral hypoperfusion have been suggested to be an important causal factor [3,6]. However, as there is no clear evidence to support this hypothesis, debate remains [3,6].…”
Section: Introductionmentioning
confidence: 99%